2007
DOI: 10.1016/j.neuroscience.2007.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Beta-amyloid disrupted synaptic vesicle endocytosis in cultured hippocampal neurons

Abstract: Neuronal death leading to gross brain atrophy is commonly seen in Alzheimer's disease (AD) patients. Yet, it is becoming increasingly apparent that the pathogenesis of AD involves early and more discrete synaptic changes in affected brain areas. However, the molecular mechanisms that underlie such synaptic dysfunction remain largely unknown. Recently, we have identified dynamin 1, a protein that plays a critical role in synaptic vesicle endocytosis, and hence, in the signaling properties of the synapse, as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 68 publications
6
66
0
Order By: Relevance
“…The accumulation of tau in ALS motor neurons provided evidence of an alternative molecular mechanism by which excitotoxicity could lead to neurodegeneration of motor neurons. In contrast to what has been described in AD and other tauopathies, calpain dysregulation in the context of ALS does not lead to aberrant cleavage of dynamin 1 ( Vintilescu and Ferreira, unpublished observations, see also 61,62). This protein is involved in the recycling of synaptic vesicles and could be responsible for synaptic dysfunction underlying the cognitive deficits characteristic of these diseases.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The accumulation of tau in ALS motor neurons provided evidence of an alternative molecular mechanism by which excitotoxicity could lead to neurodegeneration of motor neurons. In contrast to what has been described in AD and other tauopathies, calpain dysregulation in the context of ALS does not lead to aberrant cleavage of dynamin 1 ( Vintilescu and Ferreira, unpublished observations, see also 61,62). This protein is involved in the recycling of synaptic vesicles and could be responsible for synaptic dysfunction underlying the cognitive deficits characteristic of these diseases.…”
Section: Discussionmentioning
confidence: 89%
“…The calpain dysregulation observed in AD culture and animal models was induced by enhanced extracellular calcium influx mediated by glutamate N-methyl-D-aspartate (NMDA) receptors (61,62). Glutamate excitotoxicity has also been of endogenously generated tau in the context of neurons that develop in situ versus those detected when the recombinant tau fragment is incubated in the presence of an inducer of aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that, in addition to synapse loss and cell death, the deposition of WT Aβ oligomers induced synaptic dysfunction and neurite degeneration in mature hippocampal neurons (4,5,9,10,23,27). The synaptic dysfunction observed in the presence of WT Aβ was mediated, at least in part, by a decrease in dynamin 1 levels due to calpain-mediated cleavage both in cultured hippocampal neurons and in an AD animal model system (4,5,9).…”
Section: Dutch Mutant Aβ Had Differential Effects On Calpain-mediatedmentioning
confidence: 99%
“…The synaptic dysfunction observed in the presence of WT Aβ was mediated, at least in part, by a decrease in dynamin 1 levels due to calpain-mediated cleavage both in cultured hippocampal neurons and in an AD animal model system (4,5,9). To test whether E22Q Aβ has similar synaptic effects, we analyzed dynamin 1 levels in cultured hippocampal neurons incubated in the presence of increasing concentrations of this mutant Aβ form.…”
Section: Dutch Mutant Aβ Had Differential Effects On Calpain-mediatedmentioning
confidence: 99%
See 1 more Smart Citation